2021
DOI: 10.5194/bg-18-4733-2021
|View full text |Cite
|
Sign up to set email alerts
|

Host-influenced geochemical signature in the parasitic foraminifera <i>Hyrrokkin sarcophaga</i>

Abstract: Abstract. Hyrrokkin sarcophaga is a parasitic foraminifera that is commonly found in cold-water coral reefs where it infests the file clam Acesta excavata and the scleractinian coral Desmophyllum pertusum (formerly known as Lophelia pertusa). Here, we present measurements of the trace element and isotopic composition of these parasitic foraminifera, analyzed by inductively coupled optical emission spectrometry (ICP-OES), electron probe microanalysis (EPMA) and mass spectrometry (gas-source MS and inductively-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
(180 reference statements)
1
2
0
Order By: Relevance
“…Macroscopically visible darker seasonal bands and thus areas with low growth rates coincide with higher Mg/Ca, as has previously been shown in other mollusks (e.g., Lorens & Bender, 1977;Schleinkofer et al, 2021). Here, we demonstrate one advantage of deriving a continuous growth rate model by testing whether Mg/Ca and other elemental ratios correlate with the growth rates determined (Figure 7).…”
Section: El/ca Variability With Growth Ratesupporting
confidence: 82%
See 1 more Smart Citation
“…Macroscopically visible darker seasonal bands and thus areas with low growth rates coincide with higher Mg/Ca, as has previously been shown in other mollusks (e.g., Lorens & Bender, 1977;Schleinkofer et al, 2021). Here, we demonstrate one advantage of deriving a continuous growth rate model by testing whether Mg/Ca and other elemental ratios correlate with the growth rates determined (Figure 7).…”
Section: El/ca Variability With Growth Ratesupporting
confidence: 82%
“…This might be due to the impact of reduced growth during the night, characterized by elevated Mg/Ca values, and vice versa (cf., Warter et al., 2018). In bivalves, reduced growth and elevated Mg/Ca values can also be coupled to a relative increase in organic content (Schleinkofer et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of the Faroe Islands archipelago, these protists were found in the pinacoderm of all studied sponges of the family Geodiidae (Klitgaard, 1995). The most common species were Cibicides refulgens and Hyrrokkin sarcophaga, the latter described as a parasite of corals and bivalves (Schleinkofer et al 2021). Histological approaches have shown that in the sponges Isops phlegraei (now accepted as Geodia phlegraei) and Stelleta normani, the foraminifera H. sarcophaga can dissolve part of the cortex of the animal (Cedhagen, 1994).…”
Section: Sar: Rhizariamentioning
confidence: 97%